Comparison of Azithromycin and Doxycycline in Treatment of Acute Uncomplicated Pelvic Inflammatory Disease - K.C., Kanchan; Thapa, Raj Kumar (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Pelvic inflammatory disease (PID) refers to an infectious and inflammatory disorder of the female upper genital tract. It is common among young sexually active individuals and is a major health problem both in the developed and developing countries. It is usually a polymicrobial infection, however, Chlamydia trachomatis (serovars D-K) is the commonest causative agent transmitted sexually. PID is diagnosed basically by history and clinical examination and the treatment is initially empiric. Doxycycline is a good old drug in use for PID and Azithromycin is a new macrolide with promising effects for same. This comparative study aimed to measure efficiency and compliance of once daily for five days Azithromycin with twice a day for 14 days Doxycycline in the treatment of mild, uncomplicated acute PID. Methods: A descriptive cross-sectional study was conducted in randomly selected 100 consecutive outpatients with mild uncomplicated acute PID. Comparative outcome of Azithromycin and Doxycycline in correlation with reduction of amount, consistency and malodor of vaginal discharge along with reduction in fornical tenderness, compliance and frequency of adverse drug reactions was done. Comparison of categorical variables was done by chi-square test with p-value <0.05 as statistically significant. Results: Among 100 cases 50 (50%) were treated with tablet Azithromycin and 50 (50%) with tablet Doxycycline. Comparative analysis on reduction of amount, consistency, malodor of vaginal discharge and reduction of fornical tenderness were statistically significant (p < 0.05), showing Azithromycin more effective than Doxycycline. Besides, compliance was better and there were less adverse drug reactions with Azithromycin. Conclusion: Azithromycin has better efficiency and compliance over Doxycycline in the treatment of mild, uncomplicated, acute PID.